Mapping the Role of Corporate Entrepreneurship in Realizing Sustainable Business Based on SDGs - Loso Judijanto; Ardi Azhar Nampira; Diana Suksesiwaty Lubis; Syahrani Devi (West Science Journal Economic and Entrepreneurship, 2025)
This study explores the role of corporate entrepreneurship in fostering sustainable business practices aligned with the Sustainable Development Goals (SDGs) through a qualitative analysis of five informants. Findings highlight that corporate entrepreneurship drives innovation, identifies sustainability opportunities, and supports risk-taking for long-term gains. However, challenges such as balancing profitability with sustainability, stakeholder misalignment, and resource constraints persist. The study emphasizes strategic approaches, including integrating sustainability into organizational visions, fostering cross-departmental collaboration, and engaging stakeholders to overcome these challenges. The findings contribute to the understanding of corporate entrepreneurship as a lever for achieving SDGs and provide actionable insights for practitioners and policymakers.